Fifteen years of research on self & identity in System. (August 2016) - Kostoulas, Achilleas; Mercer, Sarah
Abstract: This is the second in a series of Virtual Special Issues published by System, which showcase selected articles that have appeared in the journal. In this issue, we focus on the psychological construct of the self in language teaching and learning, as viewed from diverse theoretical perspectives. Forty articles published in the last 15 years were reviewed, of which ten were selected for inclusion in this issue, taking into account their impact, their conceptual salience or their potential to exemplify theoretical developments in the field. In doing so, we draw attention to the theoretical and methodological diversity of research into the self, as represented in the journal. We identify three milestones in research, which seem to be associated with high-impact publications, but, at the same time, we note the continued presence of certain key self constructs. In addition, we trace changes in the ways that the self has been conceptualised and researched. Finally, we point out a tendency to report on aspects of the self that relate to language learners, rather than teachers, which appears to be typical of much research into language learning psychology.